Penilaian Keberhasilan Pengelolaan Program Penyediaan Air Minum dan Sanitasi Berbasis Masyarakat (PAMSIMAS) di Kabupaten Aceh Besar Provinsi Aceh - Rizki Wahyuni; B. S. Wignyosukarto; B. Kamulyan (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2021)
The PAMSIMAS program is one of the government programs supporting the national program to achieve 100% access to drinking water and sanitation. The PAMSIMAS program also facilitates and cleans proper sanitation, living, and healthy behavior. This study aims to provide an overview of the PAMSIMAS program's implementation in Lam Reh Village, Lambaro Sukon Village, and Lambaro Biluy Village in Aceh Besar District. The research also identifies factors of program sustainability and assesses the PAMSIMAS program in each village so that the facilities built by the PAMSIMAS program can be used properly.This study uses a quantitative approach using inductive methods. The data used are secondary data and primary data supported by interviews with actors related to the district and village PAMSIMAS program. The analysis used is descriptive qualitative analysis. This study's results indicate that Lam Reh and Lambaro Sukon Villages' belief is already in the Very Good category. Several variables, such as water sources, PHBS, community management, and facilities functioning, are more than 50%. However, for Lambaro Biluy Village, community management and functioning of the facilities were 44.4% and 0%, respectively, the drinking water facilities built by the PAMSIMAS program are no longer functioning.